Innovating Service and Marketing to Succeed Market-Based Marketing Performance Adoption - Hendra Riofita (The Asian Journal of Technology Management (AJTM), 2025)
Abstract. This study aims to mediate network empowerment effect on market-based marketing performance of Indonesian private Islamic higher education (PIHE) through e-service & marketing. The respondents of this survey study are 265 elements of the leaders organizing Indonesian PIHE taken using purposive, multi-stage, and simple random sampling methods. The data is taken using the questionnaire sent via Google form link to the respondents through the assistance of 15 coordinators of Coordination of Indonesian PIHE and analyzed using SPSS and SEM with Amos program. e-service & marketing mediates network empowerment effect on market-based marketing performance fully. Network empowerment positively influences market-based marketing performance and           e-service & marketing does either. In addition, network empowerment also positively influences e-service & marketing. The findings confirm that network empowerment and e- service & marketing are the resources and capabilities intended by resources-Based View Theory (RBV) which can enhance institutional market-based marketing performance as well as prospective students.  As implication, PIHE must plan and employ the constructs to be marketing strategy in highly competitive market.  Keywords: Network, e-marketing, e-service, Marketing Performance, and Higher Education